Dari Kekerasan Menuju Kesehatan Mental: Studi Kasus Konseling Realita pada Pelaku Kekerasan Seksual - Sari, Permata; Prasetyo, Agung; Bulantika, Siti Zahra; Utami, Ferisa Prasetyaning (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
Sexual violence is a serious problem that has deep psychological, physical and social impacts on victims and perpetrators. This study aims to examine the effectiveness of Reality counseling in helping male perpetrators of sexual violence overcome identity conflicts, modify maladaptive behavior, and improve their adaptation skills. This case study uses a qualitative approach with in-depth interviews and participant observation to analyze the effectiveness of Reality counseling for a perpetrator of male sexual violence against men. The study results showed that this therapy was successful in changing the perpetrator's behavior and emotional responses, and contributed to his emotional well-being while reducing the risk of relapse. Future research needs to explore the long-term effectiveness of Reality counseling in different contexts and individual characteristics to further deepen rehabilitation strategies for sexual assault perpetrators.